Intervención psicopedagógica para un estudiante del Octavo grado con dificultades específicas del aprendizaje de la Unidad Educativa Fiscomisional San Jun Bautista, 2023 - Jiménez Salazar., Kerly del Rocio (2023)
The present work of curricular integration had as objective: to develop a psycho-pedagogical intervention according to the needs presented by the student with specific difficulties in reading, writing and calculus that facilitates the process of learning and eliminates the barriers that their difficulties create in the environment; in relation to the methodology of the investigation, he responds to the qualitative approach, descriptive type, of transversal cut and method of study. For the collection of information we used the observation and psycho-pedagogical record; and the PROLEC-R test, the PROESC, the mathematical knowledge scale (Benton and Luria), the learning observation scale for tutor teachers and the learning achievement record. In the results obtained, we found that the student presents difficulties in lexical, syntactic and semantic processes both in reading and writing, and in calculus, also presents difficulties in solving operations, due to the fact that mental and written calculations are difficult. With the implementation of the intervention plan, it can be concluded that the student improved significantly and achieved to maintain more attention than in the initial activities and to understand the orders given to him. Therefore, it is recommended to continue with the application of the plan as a model to build new activities, so that, in this way, students with learning difficulties can be favored.